Mixed Production of Filamentous Fungal Spores for Preventing Soil-Transmitted Helminth Zoonoses: A Preliminary Analysis. (21st April 2013) - Arias, M. S.; Cazapal-Monteiro, C. F.; Suárez, J.; Miguélez, S.; Francisco, I.; Arroyo, F. L.; Suárez, J. L.; Paz-Silva, A.; Sánchez-Andrade, R.; Mendoza de Gives, P.
Abstract : Helminth zoonoses are parasitic infections shared by humans and animals, being the soil-transmitted helminths (STHs) mainly caused by roundworms (ascarids) and hookworms. This study was aimed to assess the individual and/or mixed production of two helminth-antagonistic fungi, one ovicide ( Mucor circinelloides ) and other predator ( Duddingtonia flagrans ). Fungi were grown both in Petri plates and in a submerged culture (composed by water, NaCl, Na2 HPO4 · 12 H2 O, and wheat ( Triticum aestivum )). A Fasciola hepatica recombinant protein (FhrAPS) was incorporated to the cultures to improve fungal production. All the cultured plates showed fungal growth, without difference in the development of the fungi when grown alone or mixed. High counts of Mucor spores were produced in liquid media cultures, and no significant differences were achieved regarding single or mixed cultures, or the incorporation of the FhrAPS. A significantly higher production of Duddingtonia spores after the incorporation of the FhrAPS was observed. When analyzing the parasiticide efficacy of the fungal mixture, viability of T. canis eggs reduced to 51%, and the numbers of third stage cyathostomin larvae reduced to 4%. It is concluded, the capability of a fungal mixture containing an ovicide ( Mucor ) and a predator species ( Duddingtonia ) for growing together in a submerged medium containing the FhrAPS offers a very interesting tool for preventing STHs.